Analysis of developmental characteristics and dominant factors of fractures in Lower Cambrian marine shale reservoirs: A case study of Niutitang formation in Cen’gong block, southern China - Wang, Ruyue; Ding, Wenlong; Zhang, Yeqian; Wang, Zhe; Wang, Xinghua; He, Jianhua; Zeng, Weite; Dai, Peng (Journal of petroleum science & engineering, 2016)
Fractures are important to shale gas reservoirs because they can increase the storage spaces and seepage pathways. In addition, natural fracture systems are important to hydraulic-fracture stimulation to form fracture networks. Currently, China has achieved a breakthrough of the Lower Silurian Longmaxi formation in Sichuan basin and its surrounding areas. Compared with the Longmaxi shale, the Lower Cambrian Niutitang shale has greater TOC content, depositional thickness and wider distribution areas; thus, it is another significant stratum for China's shale gas. This paper discusses the characteristics and dominant factors of fractures and their relationship to the gas content in the Niutitang shale based on several types of data: observations and descriptions of fracture systems in outcrops, drilling cores, casting thin sections and field-emission scanning electron microscopy (FE-SEM); detailed fracture characteristics and parameters; and analyzes and tests of corresponding fracture segment samples. The results indicate that the Niutitang shale has similar brittle mineral and TOC content as Barnett shale, except that it has a higher maturity (equivalent Ro>2.2%). Multiple types of fractures are abundant and have suffered multi-stage activation and modification; these are mainly structural fractures due to the late diagenetic stage and multi-stage tectonic movements in southern China. The primary types of micro-fractures are interlayer, inter-particle and intra-particle fractures. The fractures with scratches have abundant pores in mylonitic minerals, and unsealed fractures (inter-particle, intra-particle fractures, and cleavages) and pores (inter-particle, intra-particle and dissolved) in the cement of the fractures and have improved the effectiveness of sealed fractures. The development of fractures is controlled by structural factors, mineral composition, TOC, reservoir heterogeneity, lithology and rock mechanical properties, and the structural factor is the uppermost. Within the same tectonic setting, the content of the brittle minerals, brittleness (rock mechanical properties), and heterogeneity are positively correlated with the fracture density. When the TOC is less than 6.5wt%, the fracture density, porosity and brittleness display positive correlations with TOC; however, when the TOC is greater than 6.5wt%, the positive correlations become negative. The high quartz content (rigid particles), which is usually accompanied with high TOC, favors the development and preservation of micro-pores and fractures. Fractures have played important roles in seepage pathways, storage spaces, and interconnections of isolated micro-pores, which leads to positive correlations between the fracture density, total and desorbed gas content. Knowledge regarding this area will guide the exploration and development of shale gas and is helpful in optimizing the intervals of drilling and fracturing stimulation. •The reservoir characteristics of high maturity marine shale in southern China.•The types and developmental characteristics of fractures in Niutitang shale (є1).•The effects of fractures on shale reservoir and gas content.•The controlling factors and their interrelations of fractures in Niutitang shale.•The TOC plays a significant role in influencing the shale reservoir properties.